REALISASI DANA CSR, TATA KELOLA CSR, DAN MANAJEMEN STRATEJIK KEBERLANJUTAN TERHADAP PENGUNGKAPAN SDGS - Wisnu Setyawan; Nanny Dewi Tanzil; Dini Rosdini (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
COP26 in Scotland it was agreed that real implementation is needed in the agreements on emission reductions and related to global warming and climate change. Indonesia has consistently included these issues in the SDGs framework. Disclosure of SDGs in the Sustainability Report (SR) when viewed from the institutional isomorphism theory is a mimetic stage, where corporations make changes in order to adapt themselves to generally accepted standards (GRI). With an institutional isomorphism theory approach, this study aims to explain the factors that influence the use of SDGs in SR. Using SDGs data on SR of companies operating in Indonesia for the 2018-2020 reporting period. From 231 obtained 136 SR that meet the research criteria, and then processed by testing statistical regression analysis. The results show that the SDGs in SR are influenced by CSR governance and corporate strategic management. Where in this study these two factors are normative stages in institutional isomorphism related to the implementation of SDGs and CSR.